ZPBP and fertility-associated proteomes as novel biomarkers: A shotgun proteomics approach in Murrah buffalo (Bubalus bubalis) bulls’ seminal plasma and cryopreserved spermatozoa - Hikmayani Iskandar; Syahruddin Said; Tulus Maulana; Ekayanti Mulyawati Kaiin; Berlin Pandapotan Pardede; Isyana Khaerunnisa; Widya Pintaka Bayu Putra; Raden Iis Arifiantini; Fuad Hasan; Göran Andersson; Sarmin Sarmin; Claude Mona Airin; et al. (PLoS ONE, 2025)
Comprehensive identification of seminal plasma and spermatozoa proteins is essential to understand sperm biology and the molecular mechanisms underlying bull fertility. In this study, we conducted a quantitative proteomic analysis of seminal plasma and cryopreserved spermatozoa from Murrah buffalo ( Bubalus bubalis ) bulls using a comparative shotgun proteomics approach to identify proteins associated with reproduction. 1,893 and 1,913 proteins were identified in seminal plasma and spermatozoa, respectively. Among these, 232 proteins were selectively identified in both seminal plasma and spermatozoa. Notably, zona pellucida binding protein (ZPBP) was explicitly expressed in spermatozoa, while no reproduction-associated proteins were detected in the seminal plasma proteome. Gene ontology (GO) analysis revealed that most proteins were involved in reproduction-related cellular and metabolic processes. Protein–protein interaction (PPI) network analysis further indicated that ZPBP is involved in biological processes, including acrosome formation and spermatid development. ZPBP was identified with a low false discovery rate (FDR = 0.0021), underscoring its statistical significance. Several proteins were associated with key reproductive functions, including spermatogenesis, sperm motility, energy metabolism, and cellular stress responses. These findings reveal distinct proteomic signatures with strong potential as candidate biomarkers for assessing bull fertility, supporting more accurate reproductive evaluations, and the strategic selection of genetically and reproductively superior breeding bulls in buffalo reproductive management programs.